A comparative study of condoms and needles distribution in United States, Iran and Malaysia as a method of controlling HIV/Aids / Nasriah Nusral and Siti Jasmine Zulkifli - Nusral, Nasriah; Zulkifli, Siti Jasmine (2008)
This research paper of comparative study between the United States, Iran and Malaysia on the program of condoms and needles distribution in controlling HIV/AIDS started out with the main objective as to study whether the scheme is the best and had effectively achieved its aim. It looks at the different approaches that each country had to the implementation of the program; the liberalism of the States, the restrictive approach of the Islamic country, and the justification that each country had to establish such scheme. Furthermore, the challenges and implications that each country had in the initial stage of implementation of the program will be studied as to make the analysis to prevent such problems from occurring. From the legal point of view, the legal background of each country will be studied and whether the implementation of the program had influenced or affected the respected legal system. Interviews will be conducted from the syariah and the criminal perspectives as to Malaysia's justification in implementing such scheme. The effectiveness of the selected countries on the program will be inferred and a conclusion will be made on what would be the best method in controlling HIV/AIDs. Recommendations would also be given as to how the government could overcome the challenges faced.